2022
DOI: 10.3390/cancers14143377
|View full text |Cite
|
Sign up to set email alerts
|

Integrin β1 in Pancreatic Cancer: Expressions, Functions, and Clinical Implications

Abstract: Pancreatic cancer (PC) is characterized by rapid progression and a high mortality rate. The current treatment is still based on surgical treatment, supplemented by radiotherapy and chemotherapy, and new methods of combining immune and molecular biological treatments are being explored. Despite this, the survival rate of PC patients is still very disappointing. Therefore, clarifying the molecular mechanism of PC pathogenesis and developing precisely targeted drugs are key to improving PC prognosis. As the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 228 publications
(242 reference statements)
0
10
0
Order By: Relevance
“…Integrins typically occur on the surface of cell membranes only for a limited period of time [ 13 ]. The presence or absence of integrins has a huge influence on the capacity of malignant tumours to invade and destroy local tissue, thus also on the metastasis of tumour cells [ 14 ]. A key factor in the carcinogenesis of pancreatic carcinoma is the family of NFAT (nuclear factor of activated T-cells) transcription factors [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Integrins typically occur on the surface of cell membranes only for a limited period of time [ 13 ]. The presence or absence of integrins has a huge influence on the capacity of malignant tumours to invade and destroy local tissue, thus also on the metastasis of tumour cells [ 14 ]. A key factor in the carcinogenesis of pancreatic carcinoma is the family of NFAT (nuclear factor of activated T-cells) transcription factors [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, reports have shown that pancreatic adenocarcinoma remains refractory to conventional chemotherapeutics primarily because of the disease’s genetic heterogeneity and dense stroma, which inhibits penetration and accumulation of chemotherapeutics at the tumor sites. Hence, to improve the efficiency of pancreatic cancer therapy, selective penetration and accumulation of cytotoxic agents must be enhanced [ 19 , 35 , 110 ].…”
Section: Recent Advances In Pancreatic Cancer Targeted Therapy and Li...mentioning
confidence: 99%
“…Endoscopic ultrasound is also widely used in diagnosis in conjunction with other diagnostic techniques due to its ability to detect microscopic lesions [ 34 ]. However, early detection in patients does not automatically translate into reduced mortality; <35% of patients eligible for surgical intervention have a five-year rate of survival and approximately 85% of patients will experience a recurrence two years after surgery [ 11 , 16 , 18 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mainly early diagnosis of pancreatic cancer is difficult, and most patients are already in the late stage when diagnosed and cannot undergo surgical resection [3] . Understanding how pancreatic cancer starts and progresses, and discovering new treatments and drugs, can help patients with pancreatic cancer live longer and better [4] . Epidermal Growth Factor Receptor (EGFR) is a receptor that adds phosphate groups to tyrosine residues and regulates many cell processes, such as growth, movement, invasion, and death [5] .…”
mentioning
confidence: 99%